A Critical Review of the Effects of Nicotine and Alcohol Coadministration in Human Laboratory Studies. (3rd February 2017) - Dermody, Sarah S.; Hendershot, Christian S.
Abstract : Simultaneous use of cigarettes and alcohol is common and may be driven by nicotine increasing alcohol self‐administration or vice versa. To better evaluate the causal nature of this relationship, we systematically reviewed human experimental laboratory studies that coadministered nicotine and alcohol with control conditions. Searches of PubMed/MEDLINE and PsycINFO databases and study bibliographies identified 30 studies that met our inclusion criteria. Research methodologies were critically reviewed. Effects of coadministration on drug self‐administration and related factors such as craving, subjective response, motivation, and heart rate are reported. Results most strongly supported that alcohol increases nicotine and cigarette self‐administration, whereas, depending on the context, nicotine increased, decreased, or had no effect on alcohol self‐administration. Craving and subjective drug effects were also impacted by coadministration. Interaction effects of nicotine and alcohol on self‐administration and subjective responses were reported infrequently. The effects may be moderated by a number of factors, including dose of administered drug and sex. Recommendations are made for future research, and clinical and policy implications of findings are discussed. Abstract : By systematically and critically reviewing human experimental laboratory studies that co‐administered nicotine and alcohol, we supported that alcohol increases nicotine and cigarette self‐administration; whereas, depending on the context, nicotine increased, decreased, or had no effect on alcohol self‐administration. Craving and subjective drug effects were also impacted by co‐administration. Interaction effects of nicotine and alcohol on self‐administration and subjective responses were reported infrequently. Recommendations are made for future research and clinical and policy implications of findings are discussed.